Rise of the earth dragon ebook - West, Tracey (Dragon Masters, 2014)
The New York Times bestselling Dragon Masters series is "How to Train Your Dragon" meets the Dragon Slayers' Academy, and it's perfect for newly independent readers! Pick a book. Grow a reader. This series is part of Scholastic's early chapter book line called Branches, which is aimed at newly independent readers. With easy-to-read text, high-interest content, fast-paced plots, and illustrations on every page, these books will boost reading confidence and stamina. Branches books help readers grow! DRAGON MASTERS has it all! Dragons, a Dragon Stone, a king, a wizard, and magic! In the first book in this fully-illustrated series, 8-year old Drake is snatched up by King Roland's soldier and taken to the castle. He is to be trained as a Dragon Master. At the castle, he is joined by three other young Dragon Masters-in-training: Ana, Rori, and Bo. The Dragon Masters must learn how to connect with and train their dragons—and they must also uncover their dragons' special powers. Does Drake have what it takes to be a Dragon Master? What is his dragon's special power?